Development issues: presentations to the 49th meeting of the Development Committee, Madrid - October 3, 1994 (Washington DC The World Bank, 1994)
The Development Committee held its meeting in Madrid, Spain on October 3, 1994. The two main items on the agenda were: aid effectiveness, and the impact of the Uruguay Round on the developing and transition economies
osc 7/09/2021
Loans
Keywords: Economic Development